Quantifying changes in global health inequality: the Gini and Slope Inequality Indices applied to the Global Burden of Disease data, 1990–2017. Issue 5 (September 2019) - Steinbeis, Fridolin; Gotham, Dzintars; von Philipsborn, Peter; Stratil, Jan M
Abstract : Background: The major shifts in the global burden of disease over the past decades are well documented, but how these shifts have affected global inequalities in health remains an underexplored topic. We applied comprehensive inequality measures to data from the Global Burden of Disease (GBD) study. Methods: Between-country relative inequality was measured by the population-weighted Gini Index, between-country absolute inequality was calculated using the population-weighted Slope Inequality Index (SII). Both were applied to country-level GBD data on age-standardised disability-adjusted life years. Findings: Absolute global health inequality measured by the SII fell notably between 1990 (0.68) and 2017 (0.42), mainly driven by a decrease of disease burden due to communicable, maternal, neonatal and nutritional diseases (CMNN). By contrast, relative inequality remained essentially unchanged from 0.21 to 0.19 (1990–2017), with a peak of 0.23 (2000–2008). The main driver for the increase of relative inequality 1990–2008 was the HIV epidemic in Sub-Saharan Africa. Relative inequality increased 1990–2017 within each of the three main cause groups: CMNNs; non-communicable diseases (NCDs); and injuries. Conclusions: Despite considerable reductions in disease burden in 1990–2017 and absolute health inequality between countries, absolute and relative international health inequality remain high. The limited reduction of relative inequality has been largely due to shifts in disease burden from CMNNs and injuries to NCDs. If progress in the reduction of health inequalities is to be sustained beyond the global epidemiological transition, the fight against CMNNs and injuries must be joined by increased efforts for NCDs.